2022
DOI: 10.1038/s41598-022-18063-5
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-dependent effects of effusol and juncusol from Juncus compressus on seedling development of Arabidopsis thaliana

Abstract: Juncus species are valuable sources of phenanthrene compounds that have been used in traditional Chinese medicine for thousands of years. Effusol and juncusol are the most investigated compounds reported to have antimicrobial and anticancer effects; however, to date, their effects on higher plants have not been investigated. In this study, we examined the effects of effusol and juncusol on the growth and other biochemical parameters of the dicot model plant Arabidopsis thaliana in a concentration-dependent man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…The results of this study indicate that lower concentrations of blanket flower extracts led to an increase in seedling mass compared to the higher concentration, and to a somewhat insignificant extent compared to the control (Figure 4). This outcome aligns closely with the findings of Bakacsy et al (2022), who tested the effect of Juncus compressus purified extracts on A. thaliana seedlings. They found that juncusol increased the biomass of test plants in the applied lower concentrations (0.1 and 0.5 mM) compared with the control, with no significant difference observed in the higher‐concentration treatment.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study indicate that lower concentrations of blanket flower extracts led to an increase in seedling mass compared to the higher concentration, and to a somewhat insignificant extent compared to the control (Figure 4). This outcome aligns closely with the findings of Bakacsy et al (2022), who tested the effect of Juncus compressus purified extracts on A. thaliana seedlings. They found that juncusol increased the biomass of test plants in the applied lower concentrations (0.1 and 0.5 mM) compared with the control, with no significant difference observed in the higher‐concentration treatment.…”
Section: Discussionsupporting
confidence: 91%
“…), and root exudation [11,12]. This concept can encompass both positive and negative effects and, therefore, they are gaining increasing attention in agriculture as potential natural herbicides [13,14] in natural ecosystems; these types of plant interactions are of fundamental importance [15,16]. Allelopathic compounds may also play a protective role in a number of invasive plants [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Research on allelopathy has predominantly focused on allelochemicals and in vitro germination assays, so, for example, soil-based treatments and/or longer time course studies are less commonly used. In addition, little is known about the effects on root development, architecture, and morphology [47], even though such compounds affect the development of neighboring plants through the root in addition to germination [16,47] and thus also affect above-ground parts (shoots) [14]. Therefore, by studying allelopathy in a plant-soil or root-soil system, we can now move closer to more complex systems that better model the field environment and we can thus better understand the role of allelopathy in natural communities.…”
Section: Introductionmentioning
confidence: 99%
“…After extraction and solvent-solvent partition, the concentrated CHCl3-soluble fraction of J. maritimus was separated by VLC on silica gel with a gradient system of cyclohexane-EtOAc-MeOH. This separation yielded 14 main fractions (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). All major fractions were purified at first by column chromatography on Sephadex LH-20 gel using CH2Cl2-MeOH (1:1) as eluent, and then by RP-MPLC, NP-HPLC, RP-HPLC and NP-PLC to yield 11 compounds (4, 24, 26, 30, 32-38) (Figure 3).…”
Section: Isolation Of Compounds From J Maritimusmentioning
confidence: 99%
“…After extraction of the plant material with MeOH and solvent-solvent partition with n-hexane, CHCl3 and EtOAc, the concentrated CHCl3-soluble fraction was separated by VLC on silica gel using a gradient solvent system of cyclohexane-EtOAc-MeOH to collect 14 major fractions (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In the second step, all major fractions were purified by Sephadex LH-20 gel chromatography using CH2Cl2-MeOH (1:1) as eluent.…”
Section: Isolation Of Compounds From J Ensifoliusmentioning
confidence: 99%